Social Justice as a Principle of Social Security - Olha Kuchma (Revista Direito GV)
Abstract The purpose of this paper is to determine the impact of social justice on the volume, types, and amount of social security in the distribution of benefits in society. This study approaches the direction of social policy in the state and the place of social justice in the priorities of legislative activity. Failure to keep a balance between the interests of different classes of the population leads to confrontation in society and conflicts with the authorities. The state is constantly facing challenges that require a review of traditional social security conditions. Deteriorating demographic situation and other reasons that affect the amount of funding for the social sphere are forcing authorities to make unpopular decisions that worsen the conditions of social security. Therefore, the principle of social justice and the principle of legitimate expectation must be observed when changing the legislation in the field of social security. This article proposes the definition of the compensation coefficient in legislation, and its amount should be set in a bill to amend the legislation in the field of social security. This paper also focuses on the problem of social justice in providing social security to migrants.